The bone code eaudiobook - Reichs, Kathy (Temperance Brennan, 2021)
#1 New York Times bestselling author Kathy Reichs's twentieth "brilliant" (Louise Penny) thriller featuring forensic anthropologist Temperance Brennan, whose examinations of unidentified bodies ignite a terrifying series of events. "This is A-game Reichs, with crisp prose, sharp dialogue, and plenty of suspense" ( Booklist ). On the way to hurricane-ravaged Isle of Palms, a barrier island off the South Carolina coast, Tempe receives a call from the Charleston coroner. The storm has tossed ashore a medical waste container. Inside are two decomposed bodies wrapped in plastic and bound with electrical wire. Tempe recognizes many of the details as identical to those of an unsolved case she handled in Quebec fifteen years earlier. With a growing sense of foreboding, she travels to Montreal to gather evidence. Meanwhile, health authorities in South Carolina become increasingly alarmed as a human flesh-eating contagion spreads. So focused is Tempe on identifying the container victims that, initially, she doesn't register how their murders and the pestilence may be related. But she does recognize one unsettling fact. Someone is protecting a dark secret—and willing to do anything to keep it hidden. An absorbing look at the sinister uses to which genetics can be put and featuring a cascade of ever-more-shocking revelations, The Bone Code is "a murder mystery story that races across America at the speed of fright" (James Patterson).